Pertumbuhan dan produksi tanaman sawi (Brassica juncea l.) akibat pemberian pupuk urin kelinci dengan jenis dan dosis pemberian yang berbeda - Khilmi Nur Cholisoh; Susilo Budiyanto; Eny Fuskhah (Journal of Agro Complex, 2018)
The aim of this research was to observe the effect of abbit urine fertilizer based on Local Microorganism (LoM) with different type and dosage on growth and production of mustard. The research was conducted on 2nd June to 31st August 2017 at Greenhouse of Faculty of Animal and Agricultural Science Diponegoro University, Semarang. The research was design at 3x3 factorial design with 3 replications for each. The first factor was different type of rabbit urine fertilizer .ie. non fermented rabbit urine fertilizer (A1), rabbit urine fertilizer fermented of LoM glutinous tapai (A2), rabbit urine fertilizer fermented of LoM cassava tapai (A3) and the second factor was N dosage .ie. 150 kg/Ha (B1), 175 kg/Ha (B2), and 200 kg/Ha (B3). The observed parameters were plant N uptake, plant height, fresh weight production and dry weight production. The results of the study showed that the type and dosage of rabbit urine fertilizer did not affect of the growth and the production of mustard because the amount of N that can be utilized by the plant was relatively similar, probably due to the low C/N ratio causing the relative N easily to lose because of evaporation and the leaching process. It can be concluded that rabbit urine fermented and non fermented with different of dosage did not give significant effect on growth and production of mustard. Therfore, it is more advantageous to use non fermented rabbit urine fertilizer with 150 kg/ha dosage because of time saving and lower cost. Keywords : mustard, rabbit urine, Local Microorganism (LoM), tapai, dosage.